Ethno-cultural differences in the use of alcohol and other drugs: Evidence from the Vancouver Youth Drug Reporting System - Duff, Cameron; Puri, A.; Chow, C. (2011)
This article reports on ethno-cultural differences in the use of alcohol and other drugs by using data derived from the Vancouver Youth Drug Reporting System. Data were collected between May and August 2006 among a sample of 514 youth aged 16 to 25. Statistically significant ethno-cultural differences were reported for lifetime alcohol and other drugs prevalence; alcohol and other drugs experience in the peer group; parental attitudes; and in the assessment of alcohol and other drugs prevention strategies. White and Aboriginal youth reported significantly higher rates of personal and peer group alcohol and other drugs use than other groups, whereas Chinese youth reported the lowest rates.The implications of these findings for alcohol and other drug prevention efforts are briefly discussed. Copyright © Taylor & Francis Group, LLC.